Ethernet-based automation network systems mobile laboratory: a case study in nonlinear control of water tank system - Ucun, Levent; Akbati, Onur; Cansever, Galip (Tubitak Scientific & Technological Research Council Turkey, 2015)
This paper studies an automation network configuration for the concept of a mobile laboratory establishment. The study also covers the design and implementation of a nonlinear controller for the water tank system as a case study. The design and establishment of the mobile laboratory is involved in CoNeT (Cooperative Network Training), a European Union-funded project that aims to design mobile laboratories for different uses in industrial network systems to be used for both application-oriented research and training. In addition to automation network communication and nonlinear controller design, this study also includes Modbus communication analysis and Ethernet traffic monitoring in an industrial network. Detailed analyses about the Modbus/TCP communication, such as the calculation of I/O module response time for a requested query and the update rate of each task, are also carried out by the help of the package capturing software and mirroring property of manageable switches used in the configuration of the mobile laboratory, and the results are given in tables at the end of the paper. Moreover, the real-time results of the controlled water tank system that is introduced as a case study are given by the help of graphics and tables in order to illustrate the efficiency of the implemented controller and network configuration. The obtained results illustrate that the designed nonlinear controller achieves a good tracking performance for the closed-loop system where the water level of the tank tracks the given reference signal. As the obtained results are significant for academic research, the given application-oriented examples and results are also very useful in the concept of industrial training carried out by using the proposed mobile laboratory.
Keywords: Industrial Ethernet; Modbus; mobile laboratory; automation; nonlinear control; network systems; REAL-TIME; FIELDBUS; Computer Science; Engineering